PENGARUH CSR PADA KETERIKATAN KERJA: APAKAH KEBERMAKNAAN DAN COMPASSION BERPERAN? - Bima Aji Kurniawan; Suryandari Istiqomah (BISMA: Jurnal Bisnis dan Manajemen, 2022)
This study aims to identify the effect of Corporate Social Responsibility (CSR) on employee engagement mediated meaningfulness and compassion in the hotel industry. The population of this research is employees of 3, 4, and 5-star hotels in Surakarta City. The sample was 209 employees collected through an online questionnaire using purposive sampling. Data were analyzed using PLS-SEM with the help of SmartPLS 3 software. The results showed that CSR positively affected employee engagement, meaningfulness, and compassion. Meaningfulness positively affected employee engagement and mediated the effect of CSR on employee engagement. However, compassion did not affect employee engagement and did not mediate the effect of CSR on employee engagement. CSR is an added value that sustainably maintains employee engagement and well-being. Therefore, CSR needs to be embedded in the company's work culture and long-term strategic view. Keywords: compassion, corporate social responsibility, employee engagement, meaningfulness